Increase Power Competitive MSMEs Processed Banana Arta Shinda Through Digital Marketing Training and English Education In Way Sulan Regency - Marihot Manullang; Kuras Purba; Dearlina Sinaga; Anggun Tiur Ida Sinaga; Rashmi Ranjan Panigrahi (PT. TAROMBO RESEARCH DEVELOPMENT, 2026)
The digital marketing training and English language education were carried out to enhance the competitiveness of Arta Shinda banana-based SMEs in Way Sulan District, Lampung. This program was designed to address the main challenges faced by SMEs, including low digital literacy and limited English proficiency, which hinder market expansion, especially into international markets. The training activities were conducted through lectures and face-to-face presentations, covering digital marketing strategies based on social media platforms and the introduction of basic English vocabulary in a business context. The results showed an improvement in SME owners' understanding of how to utilize digital platforms for promotion and business communication, as well as increased confidence in using English to reach international consumers. This training has positively contributed to strengthening SME capacity and encouraging sustainable business growth in the digital era.